Responsibilities of Students in Higher Education during the COVID-19 Pandemic and New Normal period - Tari, Ezra; Selfina, Elisabet; Wauran, Queency Christie (Sekolah Tinggi Theologia Jaffray, 2020)
The COVID-19 pandemic is occurring worldwide, including in Indonesia. This issue is the responsibility of all parties. In this university, ethics is the responsibility of the academic community. This paper describes the actions of students towards themselves, and the surrounding community is facing humanitarian disasters. Literature studies are used to lay down problems and find solutions. Study critical of student responsibility in higher education. They share with others with love. Its activities are sharing masks and food and conducting blood donations. Small actions that have a significant impact on society during the COVID-19 and New Normal pandemic.